Malawi : Request for an Extension of the Extended Credit Facility Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the Malawi authorities, request for a short extension (June 30, 2016) to their arrangement under the Extended Credit Facility (ECF) that is currently due to expire on May 22, 2016. The extension is needed to provide time for the authorities to implement two prior actions for completing the seventh and eighth reviews. These comprise the reconciliation of government bank accounts for the first half of FY2015/16 and another on preparing a report on the flow and stock of domestic arrears at end-2015.